Preliminary study on processing technology of white tea “Chunyu 2” from Zhejiang Province - FAN Fangyuan; CHEN Ping; LUO Wenwen; XU Wenwu; GU Zhaoqi; MAO Zufa; GONG Shuying (浙江大学学报. 农业与生命科学版, 2017)
With the development of diversification in tea consumption, white tea has increased its popularity owning to the natural- mellow taste. Up to now, the production area of white tea relatively concentrated in Fujian Province, limited yield of which is difficult to meet the demand of market. With the geographical advantage near Fujian Province, Zhejiang Province also has abundant tea resources. It is potential for Zhejiang Province to develop white tea production. This study aims at screening optimal withering and drying parameters for processing using local white tea materials of Zhejiang Province.In this study, the fresh leaves from the cultivar “Chunyu 2”, one of major tea cultivars in Zhejiang Province were selected as test materials, and treated by traditional processing technology of white tea. Optimal withering and drying parameters for processing were explored, by sensory evaluation of the made tea and quantitative determination on chemical ingredients in made tea.The results showed that the processing time varied due to differences in ambient temperature and relative humidity caused by various types of withering and drying. Compared to sunshine withering and indoor natural withering, the quality of white tea made under controlled temperature was more stable. Short- term withering at 35℃ led to the lower catechins and amino acid contents in made tea. Lower amino acid contents under short- term high- temperature withering may be mainly because of deficient protein hydrolysis. But white tea prepared by short-term high-temperature withering gained high taste score and aroma score by sensory evaluation because of taste-sweetness increasing and green-gas reducing. Meanwhile, the results also indicated that short- term high- temperature drying could facilitate chemical reaction of amino acids and other chemical compositions, reduce amino acid contents and increase aroma richness, and improve the quality of the made tea.It is concluded that the following two processing procedures are suitable for preparation of “Chunyu 2” white tea in Zhejiang Province. 1) Fresh leaves → withering at 35℃ for 25 h → drying at 50℃ for 2 h, and 2) fresh leaves → sunshine withering for 40 h → drying at 100℃ for 30 min.